Hepatotoxicity due to Clindamycin in Combination with Acetaminophen in a 62-Year-Old African American Female: A Case Report and Review of the Literature - Jerome Okudo; Nwabundo Anusim (Case Reports in Hepatology)
Clindamycin is a bacteriostatic lincosamide antibiotic with a broad spectrum. Side effects include nausea, vomiting, diarrhea, and metallic taste; however, hepatotoxicity is rare. The incidence is unknown. It is characterized by increases in aspartate and alanine transaminases. There may be no symptoms and the treatment is to stop the administration of clindamycin. We have described a 62-year-old African American female medicated with acetaminophen and clindamycin who had initially presented to the dental clinic for the evaluation of gum pain following tooth extraction. She had significantly increased levels of liver transaminases, which trended downwards on quitting the medication.